Implementación de un biodigestor anaerobio a partir de las excretas de ganado vacuno para la obtención de biogás para su utilización como gas doméstico en la hacienda “Santa Inés” provincia de Pichincha, cantón Mejía - Chicaiza López, Kleber Germán (2018)
The farm "Santa Inés", which is located in the province of Pichincha, canton Mejia, Umbria parish has a total of 50 heads of cattle generating an approximate amount of 10kg / day of excreta. These excreta were discharged directly into nearby water supplies, which caused an environmental impact in the vicinity. On the other hand, the farm consumes 15Kg / month of LPG, in a kitchen and when there is no heating system, the calves get sick due to the low temperatures. Therefore, in order to reduce the above problems, the objective is to implement a biodigester, thereby reducing environmental pollution, and the production of biogas itself, which is used as fuel to contribute to thermal and domestic needs. For the implementation of the bio-digester, accessible and low-cost materials were used that are available in the equator, such as geo-membrane and pipelines, the biol generated is used as fertilizer for crops close to the hacienda and food of the animals, in addition to the biodigester, it is avoided that excreta are discharged directly and the environmental impact is reduced.